Presentation and treatment of congenital constriction ring syndrome: case series of 12 patients - Wahegaonkar, Chandrashekhar; Patil, Bhushan; Dogra, Bharat Bhushan; Agarkhedkar, Nikhil (International Journal of Research in Medical Sciences, 2017)
Background:We intend to present our experience of varied presentation and treatment of 12 cases of congenital constriction ring syndrome. Methods: A prospective study of patients presenting with the characteristics of the congenital constriction ring syndrome was undertaken. Twelve patients made up of 7 males and 5 females were seen. The age at presentation ranged from nine days to 5 years with a mean age of 12.9 months. Nineteen limbs were affected, made up of four right upper limbs, six left upper limbs, six right lower limbs and three left lower limbs. In the upper limb malformations involved total 36 digits, arm in one case and forearm in one case; in the lower limb malformations involved total 27 toes, foot in one and leg in four cases. Types of lesions which were found: constriction rings, intrauterine amputations, simple syndactyly. Results: Treatment options ranged from observation to multi-staged operations. Surgical correction of the constriction ring was done by excision and w-plasty to prevent or alleviate lymphoedema, multiple release incisions over distal limb to reduce the edema. Conclusion: Congenital constriction ring syndrome is of uncertain aetiology and could cause morbidity in the new-born. The syndrome and its complications are amenable to corrective surgery with good results. Early intervention is desirable for a successful outcome.